Plasma urea:creatinine ratio as a biomarker of gastrointestinal bleeding in dogs with anaemia - Ben Safrany; Andrea C. Holmes; Sophie Adamantos; Caroline Kisielewicz; Florence Juvet; Laura Macfarlane; Theresa McCann; Paula Valiente Diana; Fergus Allerton (Veterinary Medicine and Science, 2023)
Abstract Background Gastrointestinal bleeding is a cause of anaemia in dogs. A reliable, non‐invasive biomarker to differentiate gastrointestinal bleeding from other causes of anaemia would be advantageous to direct clinical decisions in anaemic patients. Plasma urea:creatinine ratio is an accepted biomarker of upper gastrointestinal bleeding in human medicine. Objectives The objective of this study was to evaluate plasma urea:creatinine ratio as a biomarker of gastrointestinal bleeding in a population of dogs with anaemia. Methods This was a prospective cross‐sectional study of dogs with anaemia presenting to referral centres for the investigation of anaemia. Cases were categorised as having overt gastrointestinal bleeding (melena on presentation), occult gastrointestinal bleeding (historical and diagnostic findings consistent with gastrointestinal bleeding without melena at presentation) or anaemia of other cause (confident diagnosis other than gastrointestinal bleeding reached, normal diagnostic imaging of gastrointestinal tract). Urea:creatinine ratio at presentation was calculated by dividing urea (mg/dL) by creatinine (mg/dL). Results Ninety‐five dogs were included. Plasma urea:creatinine ratio was not significantly different between dogs with overt or occult gastrointestinal bleeding or those with anaemia of other cause (median urea:creatinine ratio 25.8, 20.7 and 22.5, respectively). No significant difference in urea:creatinine ratio was found between dogs with upper and lower gastrointestinal bleeding (median urea:creatinine ratio 19.4 and 24.6, respectively). Conclusions Plasma urea:creatinine ratio was not helpful in differentiating between dogs with anaemia resulting from gastrointestinal bleeding (overt or occult) and those with other causes of anaemia.